Evaluasi Penggunaan Alat Pelindung Diri (APD) dalam Pemilahan Sampah AMDK Gelas Plastik di Bank Sampah SiHatin - Wibowo, Eko Ari; Widyastuti; Betanursanti, Ida; Puspitasari, Anis Fadila; Pamungkas, Krisna Adhi (Fakultas Teknik Universitas Cenderawasih, 2024)
This study aims to evaluate use of finger protection PPE in process of sorting plastic glass at SiHatin Waste Bank. The waste sorting process with high risk is the process of cutting plastic cup ring. This research uses qualitative method with case study approach, interviews, and observations to identify problems and find solutions to improve comfort and safety. PPE used for three months was proven to increase safety officers by 80.95%. However, there is discomfort experienced by 18 out of 20 officers due to several factors, namely: precision movements difficulty by 90%, sweat on fingers by 60%, inappropriate size by 45% and skin irritation by 35%. The proposed solutions include using more comfortable materials and ergonomic, setting break times, and training use of PPE to increase its effectiveness. In addition, development of cutting ring tool was developed to reduce the risk of injury and increase worker productivity.